Multilevel Analysis of Ground Beetle Responses to Forest Management: Integrating Species Composition, Morphological Traits and Developmental Instability - Dominik Stočes; Jan Šipoš (Ecology and Evolution)
ABSTRACT This study evaluates the response of ground beetle (Coleoptera: Carabidae) assemblage to forest management practices by integrating species composition, body traits, wing morphology and developmental instability. Traditional approaches that rely on averaged identity‐based descriptors often overlook phenotypic plasticity and functional trait variability, potentially masking species‐specific responses to environmental changes. To address this, we applied a three‐layered analytical approach to address this gap, utilising ground beetle occurrence and morphological trait data from Podyjí National Park, Czech Republic. The first layer assessed assemblage composition with ecological and dietary preferences across control, ecotone and clearing treatments using multivariate techniques. Building on species‐level knowledge, the second layer analysed the interaction between coarse traits, such as wing morphology and fine‐scale body traits, including body size (proxied by elytron length), head width and last abdominal sternite, to assess their relationship with the different treatments. These interactions were explored as intraspecific wing plasticity can affect functional interpretations. The third layer focused on fluctuating asymmetry as an intraindividual indicator of developmental instability, examining how ground beetles respond to environmental stressors. Our findings revealed: (i) no significant impact of habitat treatments on the presence of specialist species in the assemblage analysis; (ii) analysis of morphological traits highlights the combined influence of a coarse trait, such as wing morphology, and a fine trait, such as head width, which together contribute to the partitioning of assemblages and help distinguish differences in habitat use; and (iii) FA analysis revealed a significant positive association between the second antennal segment of specialist species and litter while displaying a negative association with Collembola. This multilevel analytical framework not only confirms ecological findings but also advances our approach to habitat and species analysis, offering deeper insights into ecosystem dynamics.